Postoperative complications in the pediatric population. Malnutrition or phase angle? Which one do we use? - Díaz-Amaya, María José; Rosales-Arreola, Laura Fernanda; Hernández-Licona, Jennifer; Pérez-Guillé, Beatriz; Ignorosa-Arellano, Karen; Carmona-Librado, Silvio; González-Zamora, José; González-Ortiz, Ailema (Frontiers in Nutrition, 2024)
Background & Aims: Malnutrition increases post-operative risks like infections and prolonged stays. Pediatric assessment challenges require using anthropometric measurements and phase angle, which reflects body cell mass and health outcomes. Phase angle varies by maturation stages, making it crucial for pre-surgical evaluations alongside BMI. This study aimed to determine the relationship between nutritional status, phase angle, and postoperative complications in pediatric patients who underwent surgery. Methods: Prospective study with patients aged 3 to 17 undergoing major non-ambulatory surgery. Anthropometric measurements (weight, height, BMI Z-scores) hand grip strength, dietary intake and body composition via bioimpedance to assess phase angle were recorded. Postoperative complications were monitored, including surgical site infections, morbidity (pneumonia, inotropic support, infections, thromboembolism), and mortality. Surgical risks and pre-and postoperative conditions were documented.After the application of the selection criteria, a total of 391 patients who underwent surgery were included; 60% (n = 235) were within the range of the preschool and school-age groups. During the follow-up period, 51 (13%) patients developed at least one postoperative complication, with surgical site infections being the most common. Moreover, as phase angle decreased, the length of stay (LOS) increased in all the participants. Among children aged ≤ 12 years old, malnutrition was a risk factor for complications [OR 3.86 (1.61-9.27 95%CI)], whereas among adolescents, phase angle served as a protective factor [OR 0.63 (0.42-0.94 95%CI)].Conclusions: Significant associations were observed between nutritional status, by BMI z-score, and post-surgical complications in younger patients. Additionally, in adolescents, the phase angle emerged as a protective factor against these complications.